2011
DOI: 10.3109/08820139.2011.580408
|View full text |Cite
|
Sign up to set email alerts
|

Reduced in vivo Cytotoxicity and Increased Mycobacterial Burden Are Associated with VirulentMycobacterium tuberculosisStrains During Lung Infection

Abstract: Cytotoxic cellular responses are crucial for clearing intracellular pathogens and generating host resistance. Experimental pulmonary tuberculosis is associated with an early delay in T cell responses and with elevated lung bacterial burden during chronic infection. In this study we quantified the in vivo cytotoxicity and the mycobacterial burden from two pertinent tissues in groups of mice infected each with a mycobacterial strain of different virulence. None of the strains induced cytotoxic responses during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, studies focused on T cell mediated lysis of Mφ infected with different Mtb strains are scarce. It has been recently demonstrated that virulence of Mycobacterium strains are associated with subverting CTL responses, thus contributing to early bacterial replication and subsequent persistence in the lungs [22]. In this line, we have previously shown that strain M in vitro elicits a remarkably low CD8-dependent CTL activity in terms of ability to lyse M-pulsed Mφ and expression of the degranulation marker CD107 [11].…”
Section: Introductionmentioning
confidence: 80%
“…However, studies focused on T cell mediated lysis of Mφ infected with different Mtb strains are scarce. It has been recently demonstrated that virulence of Mycobacterium strains are associated with subverting CTL responses, thus contributing to early bacterial replication and subsequent persistence in the lungs [22]. In this line, we have previously shown that strain M in vitro elicits a remarkably low CD8-dependent CTL activity in terms of ability to lyse M-pulsed Mφ and expression of the degranulation marker CD107 [11].…”
Section: Introductionmentioning
confidence: 80%
“…Conversely, infection with smoothtype M. Canettii strains rarely cause TB in humans, and in the experimental mouse model, M. canettii strains show low cellular infiltrate with limited lung bacterial burden during chronic infection (M. Fabre et al, 2010). Importantly, among these three strains, virulence showed a direct correlation with inhibition of in vivo cytotoxicity (L. Quintero-Macias et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong & P. D. Hart, 1971) and cytotoxic CD8+ T cells (E. M. Weerdenburg et al, 2010). The analysis of these evasion mechanisms used by MTC strains, however, have barely been comparatively assessed (L. Quintero-Macias et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCs and AMs, both constituting the majority of lung antigen presenting cells (APC), defend against pulmonary infection by phagocytosing foreign particles and presenting these antigens to immune cells. Mtb specifically disrupts the function of lung APCs by causing the arrest of phagosome maturation [ 12 , 13 ], inhibition of phagosome-lysosome fusion [ 14 , 15 ], inhibition of cytotoxicity [ 16 , 17 ], and subversion of MHC-II intracellular trafficking[ 18 ]. Furthermore, Mtb delays the maturation and migration of lung dendritic cells [ 19 – 22 ].…”
Section: Introductionmentioning
confidence: 99%